2020
DOI: 10.3389/fpsyg.2020.559100
|View full text |Cite
|
Sign up to set email alerts
|

Being a Psychotherapist in Times of the Novel Coronavirus Disease: Stress-Level, Job Anxiety, and Fear of Coronavirus Disease Infection in More Than 1,500 Psychotherapists in Austria

Abstract: This study investigated stress-level, degree of job-related anxiety, and fear of coronavirus disease (COVID-19) infection in psychotherapists in the early weeks of the COVID-19 lockdown in Austria. One thousand five hundred and forty-seven psychotherapists participated in an online survey, assessing stress [Perceived Stress Scale-10 (PSS-10)], work-related worries and fears of existence [Job Anxiety Scale (JAS)], fear of COVID-19 infection during face-to-face psychotherapy, and adherence to five protective mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
3
30
1
8
Order By: Relevance
“…Even being depicted as “heroes” by the media can in fact be counterproductive, as it increases their perceived pressure ( Cox, 2020 ). This situation can significantly affect their mental health and even lead to work-related trauma ( Probst et al, 2020 ; Vagni et al, 2020 ). Many healthcare workers have been documented to have developed mental issues for which they require psychological support ( Lai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even being depicted as “heroes” by the media can in fact be counterproductive, as it increases their perceived pressure ( Cox, 2020 ). This situation can significantly affect their mental health and even lead to work-related trauma ( Probst et al, 2020 ; Vagni et al, 2020 ). Many healthcare workers have been documented to have developed mental issues for which they require psychological support ( Lai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the international literature have given insight on personal protective equipment ( Park, 2020 ), specific work risks for healthcare workers related to COVID-19 ( Ali S. et al, 2020 ), and psychological coping mechanisms (see e.g., Muller et al, 2020 ; Probst et al, 2020 ; Teo et al, 2020 ; Vagni et al, 2020 ). Further studies have shed light on risk perception and attitudes towards COVID-19 (see e.g., Führer et al, 2020 ; Hager et al, 2020 ; Honarvar et al, 2020 ; Zegarra-Valdvia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, forefront healthcare workers reported perception of the detrimental impact of COVID-19 on mental health [ 7 , 8 ]. A previous study conducted on psychotherapists during the first lockdown of the COVID-19 pandemic in Austria revealed a higher stress level compared to a representative German sample [ 9 ]. However, the mental well-being and stress level of volunteer helpers—such as counselors of telephone emergency services—have not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies addressed mental well-being in the general population, in individuals with pre-existing psychiatric disorders, as well as in forefront healthcare workers, as summarized above. Also in Austria, mental health in the general population as well as in psychotherapists has been assessed before [ 5 , 6 , 9 ]. However, the mental well-being and subjective stress level of voluntary counselors of TES have not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…In the short term, the need to adapt the format of how psychotherapy is provided might pose a specific challenge (i.e., to provide psychotherapy via the internet or telephone with all its technical and legal challenges [ 14 , 15 , 16 ]). We recently reported that during the first weeks of the COVID-19 lockdown in Austria, the average number of patients treated per week decreased and face-to-face sessions were largely substituted by sessions via telephone or internet [ 15 ]; however, despite these challenges psychotherapists were exposed to in the early weeks of the COVID-19 outbreak in Austria, job-related worries and fears of existence, as well as stress level, were neither affected by the extent of the reduction in the number of patients treated nor by the format of how psychotherapy was provided during the COVID-19 lockdown in Austria [ 17 ].…”
Section: Introductionmentioning
confidence: 99%